2017
DOI: 10.1093/toxsci/kfx032
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Nitrogen Mustard-Induced Lung Macrophage Activation by Valproic Acid, a Histone Deacetylase Inhibitor

Abstract: Nitrogen mustard (NM)-induced lung injury is associated with an accumulation of proinflammatory/cytotoxic M1 and antiinflammatory/wound repair M2 macrophages, which have been implicated in tissue injury and repair. Herein, we analyzed the effects of valproic acid (VPA), a histone deacetylase (HDAC) inhibitor with antiinflammatory and antioxidant activity, on lung macrophages responding to NM. Treatment of rats with NM (0.125 mg/kg, i.t.) resulted in structural alterations in the lung and a macrophage-rich infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 60 publications
5
23
0
Order By: Relevance
“…A rat model of spinal cord injury showed a diminished macrophage infiltration due to a reduced inflammation, which provided neuroprotection [72, 73]; likewise, VPA also reduced the macrophage infiltration in a mouse model of nephropathy [74]. In addition, a rat model of lung injury demonstrated that VPA impaired M1 macrophages and the expression of the antigen of nuclear proliferation and of oxidative stress markers, while favoring the proliferation of M2 macrophages; this was related to reduced inflammation and increased tissue repair [75].…”
Section: Effects Of Valproic Acid On Cells Of the Innate Immune Rementioning
confidence: 99%
“…A rat model of spinal cord injury showed a diminished macrophage infiltration due to a reduced inflammation, which provided neuroprotection [72, 73]; likewise, VPA also reduced the macrophage infiltration in a mouse model of nephropathy [74]. In addition, a rat model of lung injury demonstrated that VPA impaired M1 macrophages and the expression of the antigen of nuclear proliferation and of oxidative stress markers, while favoring the proliferation of M2 macrophages; this was related to reduced inflammation and increased tissue repair [75].…”
Section: Effects Of Valproic Acid On Cells Of the Innate Immune Rementioning
confidence: 99%
“…Its effects on M2s have not been elucidated although it has been shown to inhibit tumor growth enhancement induced by decoy receptor 3 which promotes M2 TAM infiltration [ 100 ]. Additionally, in a nitrogen mustard-induced lung injury model, VPA decreases iNOS + CCR2 + macrophages and increases CD68 + , CD163 + , and ATR-1a + macrophages in lung tissue [ 101 ]. In M1 in vitro models, VPA has been shown to generally decrease M1 markers and phenotype [ 88 , 102 , 103 ].…”
Section: Introductionmentioning
confidence: 99%
“…8). Cisplatin involves the DNA-damage response is time-and dose-dependant [29,30]. Cisplatin involves the DNA-damage response is time-and dose-dependant [31].…”
Section: Nicotine Increases Migration and Invasion Of Lung Cancer Celmentioning
confidence: 99%